(untitled) (Revista Contexto & Educação, 2025)
This article has the character of an announcement-denunciation, constituting a movement to hope for other possible worlds based on South-South Epistemologies, knowledge and philosophies present in Deep America. The coloniality established in America following the European invasion brought with it Euro-centered thinking, which violently denies the plural forms of being and threatens the right of existence - of the being of many lives. However, despite the oppressive nature of Euro-North-centered thought, with Sulear it finds resistance in indigenous and popular thought, in the force that gravitates from this soil, which is first and foremost indigenous. From this perspective, this work analyzes South-South epistemologies, from the perspective of the unprecedented-viable, especially in the context of education. This is a work of a bibliographic nature, centered on the works of Paulo Freire (1921-1997), Ailton Krenak (1953-) and Rodolfo Kusch (1922-1979), from which we describe the genesis of sulear and weave visibilities to the South-South, mobilizing concepts such as Epistemologies of the South, Unprecedented Viability and Good Living. The text highlights the importance of utopia, of continuing to hope and indicates that America’s strength lies in its heir and it will only build its path considering its depths and its ancestry, which is still our South.